Don't wake up the dragon! Monstrous geontologies in a mining waste impoundment. (December 2018) - Ureta, Sebastián; Flores, Patricio
This paper is an invitation to view tailings – the most prominent byproduct generated by mining activity – as more than their usual incarnation as waste, object of governance by waste management programs. In doing so, it applies Elizabeth Povinelli's notions about geontopower/geontologies to analyze the practices devoted to managing the tailings produced by Mina El Teniente, a large copper mine located in central Chile. From this framework, the mine's tailings impoundment are enacted as both a "dragon" and a "trickster", entities endowed with a monstrous vitality that openly challenges the mining industry's usual geontologies, which are based on understanding impoundments as docile nonliving deserts very much open to capitalist exploitation/forgetting. On the contrary, the dragon/trickster enacts a geontology in which human beings appear as ultimately unable to truly control nonliving entities, and depend only on their goodwill to avoid environmental disaster. The acceptance of such a geontology, as will be explored in the conclusions, challenges us to develop a geo-teratology, or a set of alternative political and ethical commitments we should devise in order to start better living with the monstrous geontologies of mining waste.